2021
DOI: 10.1111/jne.12976
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and neural responses to restraint stress in an animal model of perimenopause in female rats

Abstract: Perimenopause is clinically defined as a midlife transition state that leads to reproductive senescence in women 1,2 but, functionally, its symptoms are largely neurological in nature 3 (ie, depression, insomnia, mood changes, cognitive dysfunction, anxiety and aggressive behaviour). Worldwide, approximately 1 billion women are aged 40-60 years (United States Census Bureau, 2014) and 88% of this population will transit through perimenopause at an average age of 51.4 years. 4 Thus, all women, regardless of ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
(193 reference statements)
1
2
0
Order By: Relevance
“…Corticotropin-releasing factor (CRF) is a key component of stress responsivity, modulating related behaviors, including anxiety and reward. The primary stress response involves the activation of hypothalamic neurons producing CRF, an initial step in the cascade that leads to the synthesis and release of glucocorticoids [51][52][53][54][55][56][57]. Our data also showed the activation of CRF immunoreactive neurons in the PVN after repeated 21 days of restraint stress.…”
Section: Discussionsupporting
confidence: 59%
“…Corticotropin-releasing factor (CRF) is a key component of stress responsivity, modulating related behaviors, including anxiety and reward. The primary stress response involves the activation of hypothalamic neurons producing CRF, an initial step in the cascade that leads to the synthesis and release of glucocorticoids [51][52][53][54][55][56][57]. Our data also showed the activation of CRF immunoreactive neurons in the PVN after repeated 21 days of restraint stress.…”
Section: Discussionsupporting
confidence: 59%
“…Locus Coeruleus: Tyrosine hydroxylase (TH), the enzyme catalyzing the rate-limiting step in catecholamine biosynthesis, is frequently used in the immunohistochemical identification of noradrenergic LC neurons [ 30 , 32 ] and is even considered a noradrenergic marker of the LC [ 31 ]. It was, therefore, used here to study the LC.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, studies showed that females have higher levels of stress-induced corticosterone than males, both in basal conditions and in response to a variety of stress conditions (Albrechet-Souza et al, 2020; Babb et al, 2013; Kalil et al, 2014; Kant et al, 1983; Oyola and Handa, 2017). It is important to note that several factors can affect plasma corticosterone concentrations across the estrous cycle, including the transition period for ovarian hormonal secretion, regularity of the estrous cycle, and the phases of circadian rhythm (Arikawe et al, 2021; Atkinson and Waddell, 1997; Gong et al, 2015). In the present study, we did not investigate the plasma levels of corticosterone and ovarian hormones; therefore, future studies aimed at evaluating the influence of CBD treatment on behavioral and endocrine responses will provide additional evidence for sex-related differences in response to drug treatment.…”
Section: Discussionmentioning
confidence: 99%